Eksperimen Pembelajaran Matematika Menggunakan Strategi Ekspository Dan Inquiry Terhadap Hasil Belajar Ditinjau Dari Gender Siswa Kelas VII Semester Genap di SMP Negeri 2 ColomaduTahun 2015/2016 - Jayanti, Febrina; , Drs. Ariyanto, M.Pd (2016)
The purpose of research are (1) to examine the influence of expository learning strategies and inquiry strategies for learning outcomes of student, (2) to examine the influence of gender differences for learning outcomes of student, (3) to examine the interaction of learning strategies and gender for learning outcomes of student. The type of the research is quantitative research with quasi experimental design. The time of this research made is in the even semester 2015/2016. The population of the research is all of student seven grade at SMP Negeri 2 Colomadu, the sample of research is VIIG and VIIH graders. The technique of collecting data with methods of testing and documentation. The technique of analyzing data by using the unbalanced two-way analysis of variance. The finding of the research with α = 5%: (1) there is no influence of expository learning strategies and inquiry strategies for learning outcomes in mathematics, (2) there is no influence of gender differences for learning outcomes in mathematics, (3) there is no interaction of learning strategies and gender for learning outcomes in mathematics.